2018
DOI: 10.1016/j.scitotenv.2018.05.260
|View full text |Cite
|
Sign up to set email alerts
|

Emissions and atmospheric processes influence the chemical composition and toxicological properties of urban air particulate matter in Nanjing, China

Abstract: Ambient inhalable particulate matter (PM) is a serious health concern worldwide, but especially so in China where high PM concentrations affect huge populations. Atmospheric processes and emission sources cause spatial and temporal variations in PM concentration and chemical composition, but their influence on the toxicological characteristics of PM are still inadequately understood. In this study, we report an extensive chemical and toxicological characterization of size-segregated urban air inhalable PM coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 107 publications
1
15
0
1
Order By: Relevance
“…Initial metabolic activity and cytotoxicity assessment were carried out assessing PM concentrations ranging from 6.5 μg/ml to 100 μg/ml (see Figure S1). At 50 μg/ ml, reduced metabolic activity in cells can be observed without overt cytotoxicity, allowing for some recapitulation of cellular damage in chronic exposure to PM in vivo [3,19]. A 24-h incubation with the different PM size classes did not result in differences in LDH release into the culture medium ( Fig.…”
Section: Exposure To Pm Perturbs Cellular Metabolism In Hom Culturesmentioning
confidence: 90%
See 1 more Smart Citation
“…Initial metabolic activity and cytotoxicity assessment were carried out assessing PM concentrations ranging from 6.5 μg/ml to 100 μg/ml (see Figure S1). At 50 μg/ ml, reduced metabolic activity in cells can be observed without overt cytotoxicity, allowing for some recapitulation of cellular damage in chronic exposure to PM in vivo [3,19]. A 24-h incubation with the different PM size classes did not result in differences in LDH release into the culture medium ( Fig.…”
Section: Exposure To Pm Perturbs Cellular Metabolism In Hom Culturesmentioning
confidence: 90%
“…Urban size-segregated PM 1-0.2 , PM 2.5-1 and PM 10-2.5 were collected from Nanjing, China with a high volume cascade impactor and reconstituted as described [3]. Detailed information on the collection site, meteorology, chemistry and protocols in Table S2 in Supplementary Information and are described [3,19]. Despite high concentrations of PM in the sampling location, the mass of the ultrafine particles was relatively low.…”
Section: Pm Preparation and Exposurementioning
confidence: 99%
“…An American Cancer Society study and a large number of follow-up studies have identified ambient particulate matter (PM) mass concentrations as a health-relevant metric [9,10]. The burden of disease from particulate air pollution is mainly associated with the fine (0.1 to 2.5 µm) and ultrafine (<0.1 µm) fractions [11][12][13][14][15][16]. A range of studies also show that not only particle mass is of importance for determining health outcomes, but also other aerosol metrics, including number concentrations, surface area concentrations, and chemical composition [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“… 1 ; 2 ; 3 ; 4 ; 5 ; 6 ; 7 ; 8 ; 9 ; 10 ; 11 ; 12 ; 13 ; 14 ; 15 ; 16 ; 17 ; 18 ; 19 ; 20 ; 21 ; 22 ; 23 ; 24 ; 25 ; 26 ; 27 ; 28 ; 29 ; 30 ; 31 ; 32 ; 33 ; 34 ; 35 ; 36 ; 37 ; 38 ; 39 ; 40 ; 41 ; 42 ; 43 ; 44 ; 45 ; 46 ; 47 ; 48 ; 49 ; 50 ; 51 ; 52 .…”
Section: Uncited Referencesunclassified